T3 Altered neutrophil proteomes in COVID19 patients 29-days post hospital admission are associated with delayed recovery: results from the PREDICT-COVID19 study. (11th November 2022) - Long, MB; Brenes, AJ; Howden, AJM; Keir, HR; Rollings, C; Giam, YH; Pembridge, T; Delgado, L; Abo-Leyah, H; Lloyd, A; Sollberger, G; Hull, RC; et al.
Abstract : Introduction and Objectives: Neutrophils are increasingly recognised for a role in acute COVID19, contributing to hyperinflammatory responses, immunothrombosis and tissue damage. However, less is known about the cellular changes occurring within neutrophils in acute disease, as well as neutrophil function in patients recovering from COVID19. Mass spectrometry-based proteomics of neutrophils from hospitalised COVID19 patients sampled longitudinally was utilised to characterise these cells in both acute and long COVID19 (i.e. symptoms for ≥4 weeks). Methods: Prospective observational study of hospitalised patients with PCR-confirmed SARS-CoV-2 infection (May 2020–December 2020). Patients were enrolled within 96 hours of admission, with longitudinal sampling up to day 29. Control groups comprised hospitalised patients with non-COVID19 acute respiratory infection and age-matched non-infected controls. Neutrophils isolated from peripheral blood were processed for mass spectrometry. COVID19 severity was defined using the WHO 7-point ordinal scale. Results: 84 COVID19 patients were included (mean age±SD 65.5±14.6 years; 52.4% male), 91 non-COVID19 respiratory infection patients (age 65.7±16.7 years; 49.5% male) and 42 non-infected controls (age 58.5±17.9; 40% male). 1, 748 proteins were significantly different (q-value≤0.05) in COVID19 neutrophils compared to those of non-infected controls. Major differences included a robust interferon response at baseline, with markers of neutrophil immaturity (CD10, CD71), increased neutrophil activation (CD64), and changes in metabolism which associated with COVID19 disease severity. Delayed recovery (WHO score 2–3) at day 29 was associated with significant changes in 1, 107 proteins compared to the control population. Features of non-recovery included significantly reduced abundance of migratory receptors (e.g. C3AR1, LTB4R), integrins (CD11b, CD18), inhibitory molecules (e.g. SHP-1, SHIP-1) and indications of increased activation (CD64). Overall, ficolin and specific granule content was decreased in COVID19 patient neutrophils at day 29 compared with controls, however, comparing those who had recovered and those who had not, granule content was found to be significantly lower in the non-recovery group. Conclusion: Neutrophils undergo significant changes in acute COVID19 associated with disease severity. Neutrophil proteomics revealed that these cells may have an ongoing role in non-recovered patients, including profiles associated with increased potential for neutrophil activation and reduced migratory capacity, highlighting neutrophils as potential therapeutic targets in long COVID19.